Magnesium-based hydrogen storage material added with natural coke and transition metal and preparation method of magnesium-based hydrogen storage material

By using balls of natural coke and transition metal in magnesium-based hydrogen storage materials for mixed ball milling, the problems of low dispersion of the catalyst and difficulty in nano-nanoization of magnesium powder are solved, and the hydrogen absorption and hydrogen release kinetic properties of magnesium-based hydrogen storage materials are significantly improved.

CN119772181AActive Publication Date: 2025-04-08SHANDONG UNIV OF SCI & TECH

Patent Information

Application Number
CN202510172021.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-04-08
Estimated Expiration
2045-02-17

AI Technical Summary

Technical Problem

When the transition metal catalyst is added by the ball milling method in the prior art, the degree of dispersion of the catalyst is low and the magnesium powder is difficult to nanometer, resulting in the hydrogen absorption and hydrogen release kinetic properties of the magnesium-based hydrogen storage material not effectively improved.

Method used

The balls of natural coke and transition metal are mixed for mixed ball milling. The transition metal is transferred to the surface of magnesium particles through natural coke as a carrier, and the dispersion and grinding media of natural coke are used to make the magnesium powder easy to nano-narrow.

Benefits of technology

The dispersion degree and catalytic effect of transition metal catalysts are improved, the nanoification of magnesium powder is promoted, and the kinetic properties of hydrogen absorption and hydrogen discharge of magnesium-based hydrogen storage materials are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119772181A_ABST
    Figure CN119772181A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of hydrogen storage materials, in particular to a magnesium-based hydrogen storage material added with natural coke and transition metal and a preparation method of the magnesium-based hydrogen storage material. The preparation method comprises the following steps: under a protective atmosphere, carrying out ball milling on the natural coke, then adding transition metal balls serving as a catalyst precursor, carrying out mixed ball milling, then separating out the remaining transition metal balls after ball milling, and finally adding magnesium powder, and carrying out mixed ball milling, so as to prepare the magnesium-based hydrogen storage material added with the natural coke and the transition metal. The transition metal ground from the transition metal balls is transferred to the surfaces of the magnesium particles by taking the natural coke as a carrier, so that the dispersion degree of the transition metal catalyst is improved, and the catalytic effect of the transition metal catalyst is improved; and the magnesium powder is easy to nanocrystallize by utilizing the dispersion effect of the natural coke on the ball milling of the magnesium powder and the effect of a grinding medium, so that the technical problem that the ball milling method is difficult to realize the high dispersion of the solid catalyst and the nanocrystallization of the magnesium powder is solved, and the hydrogen absorption and hydrogen desorption dynamic performance of magnesium can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen storage materials, and in particular to a magnesium-based hydrogen storage material added with natural coke and transition metal and a preparation method thereof. Background Art

[0002] Hydrogen energy is the chemical energy released by chemical reactions between hydrogen and oxygen. Due to its high energy density, the only reaction product being water, abundant resources and sustainable development, hydrogen energy is considered to be a clean energy source with great potential and has become a research hotspot. The hydrogen storage link is crucial to the practical application of hydrogen energy. Solid materials can be used to store hydrogen. Among them, magnesium-based hydrogen storage materials are favored by researchers because of their abundant magnesium resources and high hydrogen storage density.

[0003] The poor hydrogen absorption and desorption kinetics of magnesium-based hydrogen storage materials, which are composed of magnesium alone, restrict their practical application in hydrogen energy. Adding transition metal catalysts and reducing the particle size of magnesium powder by ball milling are common technical means to improve the kinetics of magnesium-based hydrogen storage materials.

[0004] However, when the transition metal catalyst is added by ball milling, the transition metal catalyst is generally compounded with magnesium particles in the form of micrometer-scale / nanometer-scale particles, resulting in a low degree of dispersion of the catalyst on the surface of the magnesium particles and a poor catalytic effect.

[0005] When reducing the particle size of magnesium powder by ball milling, a dispersant needs to be added to prevent "cold welding" between magnesium particles during the ball milling process. However, commonly used dispersants such as graphite powder, talcum powder, and organic solvents do not have a significant grinding medium effect and it is difficult to nano-size the magnesium powder.

[0006] Therefore, the current technical means of adding transition metal catalysts and reducing the particle size of magnesium powder by ball milling have technical problems such as low dispersion of transition metal catalysts and difficulty in nano-sizing magnesium powder, resulting in the failure to effectively improve the hydrogen absorption and desorption kinetics of magnesium-based hydrogen storage materials. Summary of the invention

[0007] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a magnesium-based hydrogen storage material with added natural coke and transition metals and a preparation method thereof, which solves the technical problems of low dispersion of the catalyst added by the ball milling method and difficulty in nano-forming magnesium powder.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions:

[0009] The present invention provides a method for preparing a magnesium-based hydrogen storage material by adding natural coke and transition metal, comprising the following steps:

[0010] Under a protective atmosphere, natural coke is ball-milled to obtain natural coke powder; then transition metal pellets as catalyst precursors are added to the natural coke powder for mixed ball-milling, and then the remaining transition metal pellets after ball-milling are separated to obtain natural coke loaded with transition metals; finally, magnesium powder is added to the natural coke loaded with transition metals for mixed ball-milling to obtain a magnesium-based hydrogen storage material with added natural coke and transition metals.

[0011] The mass proportions of the components in the magnesium-based hydrogen storage material are as follows: 3.9wt% to 7.2wt% of natural coke, 0.7wt% to 1.7wt% of transition metals, and 91.2wt% to 94.9wt% of magnesium, wherein the transition metal is at least one of iron, cobalt and nickel.

[0012] The present invention transfers the transition metal ground from the transition metal balls to the surface of magnesium particles using natural coke as a carrier, so as to improve the dispersion degree of the transition metal catalyst and enhance the catalytic effect of the transition metal catalyst; and utilizes the dispersing effect of natural coke on the magnesium powder during ball milling and the grinding medium effect, so that the magnesium powder is easy to be nanosized, thus solving the technical problem that the ball milling method is difficult to achieve high dispersion of the solid catalyst and nanosize of the magnesium powder, and can effectively improve the hydrogen absorption and desorption kinetics of magnesium.

[0013] Optionally, the ball milling speed of the natural coke is 480 r / min to 600 r / min, and the ball milling time is 0.5 h to 1.5 h. More preferably, the ball milling speed is 540 r / min, and the ball milling time is 1 h.

[0014] Optionally, the ball milling speed of adding the transition metal balls to the natural coke powder for mixed ball milling is 240 r / min to 360 r / min, and the ball milling time is 2 h to 4 h. More preferably, the ball milling speed is 300 r / min, and the ball milling time is 3 h.

[0015] Optionally, the mass ratio of the transition metal pellets to the natural coke powder is 2 to 5: 1. Further preferably, the mass ratio of the transition metal pellets to the natural coke powder is 3:1.

[0016] Optionally, the ball milling speed of adding magnesium powder into natural coke loaded with transition metals for mixed ball milling is 360 r / min to 480 r / min, and the ball milling time is 1 h to 3 h.

[0017] The present invention also provides a magnesium-based hydrogen storage material added with natural coke and transition metal, which is prepared by the above-mentioned preparation method.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The present invention transfers the transition metal ground from the transition metal balls to the surface of the magnesium particles using natural coke as a carrier to improve the dispersion of the transition metal catalyst and enhance the catalytic effect of the transition metal catalyst; and utilizes the dispersing effect of natural coke on the magnesium powder during ball milling and the grinding medium effect to make the magnesium powder easy to nanosize, thereby solving the technical problem that the ball milling method is difficult to achieve high dispersion of solid catalysts and nanosize of magnesium powder, and can effectively improve the hydrogen absorption and desorption kinetics of magnesium.

[0020] Specifically, the transition metal catalyst added to the surface of the magnesium particles is ground from transition metal pellets. Compared with conventional micron-scale / nano-scale transition metal catalyst particles, the transition metal catalyst ground from transition metal pellets has a greater degree of dispersion and higher catalytic activity. Natural coke is used as a grinding aid for ball milling of magnesium powder. Natural coke has a high hardness and acts as a good grinding medium for magnesium powder. It also has a good dispersion effect on magnesium powder, which can prevent "cold welding" between magnesium particles, making it easy to grind magnesium powder to nanometer level, which is beneficial to improving the hydrogen absorption / desorption rate of magnesium.

[0021] (2) During the process of hydrogen absorption / desorption of magnesium-based hydrogen storage materials at high temperatures, natural coke plays a good confinement role on the magnesium particles, which can prevent the magnesium particles from merging and growing, and is beneficial to stabilizing the hydrogen absorption / desorption kinetics of magnesium.

[0022] (3) Natural coke is generally used as a low-value fuel due to its poor thermal stability, flammability and low chemical reactivity. However, the present invention innovatively applies it to the preparation of high-performance magnesium-based hydrogen storage materials, allowing it to be used in a high-value manner. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention provides an X-ray diffraction spectrum of magnesium powder.

[0024] Figure 2 This is a scanning electron microscope photograph of the natural coke after ball milling obtained in Example 1 provided by the present invention.

[0025] Figure 3 This is a scanning electron microscope photograph of the magnesium-based hydrogen storage material prepared in Example 1 provided by the present invention.

[0026] Figure 4 This is a distribution diagram of the nickel element in the magnesium-based hydrogen storage material prepared in Example 1 provided by the present invention.

[0027] Figure 5 This is a transmission electron microscope photograph of the magnesium-based hydrogen storage material prepared in Example 1 provided by the present invention.

[0028] Figure 6 This is an X-ray diffraction spectrum of the magnesium-based hydrogen storage material prepared in Example 1 provided by the present invention.

[0029] Figure 7 This is a graph showing the hydrogen absorption kinetics of the magnesium-based hydrogen storage material prepared in Examples 1 to 3 provided in the present invention at 200°C.

[0030] Figure 8 This is a hydrogen release kinetics curve of the magnesium-based hydrogen storage material prepared in Example 1 provided by the present invention at 300°C.

[0031] Fig. 9 This is a hydrogen absorption / desorption isotherm diagram of the magnesium-based hydrogen storage material prepared in Example 1 provided by the present invention at 300°C.

[0032] Fig.10 The cyclic hydrogen absorption / desorption kinetic curve of the magnesium-based hydrogen storage material prepared in Example 1 provided by the present invention at 300°C. DETAILED DESCRIPTION

[0033] In order to solve the above technical problems, the present invention provides a magnesium-based hydrogen storage material with added natural coke and transition metals and a preparation method thereof. The technical scheme and embodiments of the present invention are now described in detail in conjunction with the accompanying drawings.

[0034] The technical principle of the present invention is: using transition metal balls as the precursor of transition metal catalyst, zirconium dioxide with high mechanical strength as the grinding medium, and natural coke as the catalyst carrier, the transition metal balls and natural coke powder are mixed and ball-milled, and the natural coke particles with a graphite lamellae structure are ground into lamellar small particles, and the specific surface area is increased. At the same time, the transition metal ground from the transition metal balls is adsorbed on the surface of the natural coke small particles in the state of single atoms / atomic clusters. Then, magnesium powder is added for mixed ball milling. The hard natural coke particles have a good grinding medium effect on the soft magnesium particles, which is conducive to reducing the particle size of the magnesium powder. In addition, the natural coke particles have a good dispersing effect on the magnesium powder, which can prevent "cold welding" between the magnesium particles and is also conducive to reducing the particle size of the magnesium powder, so that it is easy to grind the magnesium powder to the nanoscale, thereby shortening the diffusion distance of hydrogen atoms in the magnesium crystal during the magnesium absorption / desorption process and increasing the magnesium absorption / desorption rate. At the same time, the transition metal catalyst on the surface of the natural coke particles during the ball milling process is combined with the magnesium particles in the state of single atoms / atomic clusters. Compared with the micron-scale / nano-scale granular transition metal catalyst, this reduces the amount of transition metal catalyst used and improves the catalytic effect of the transition metal catalyst on the magnesium absorption / desorption. Both the high dispersion of the transition metal catalyst and the nano-size of the magnesium powder are conducive to improving the hydrogen absorption / desorption kinetics of magnesium.

[0035] Natural coke is a product of coking bituminous coal under natural conditions in contact with magma. Gas is generally trapped in the pores and cracks of natural coke. It has no cohesiveness when heated, is explosive, has poor thermal stability, low chemical activity, and has low utilization value. The present invention uses the characteristics of natural coke, which has a graphite-like layer structure and hard texture, as a carrier of transition metal catalysts and a grinding aid for magnesium powder ball milling.

[0036] The natural coke used in the present invention is produced from the Xulou Mine Field of Tengxian Coalfield in Shandong Province. One third of the coking coal is formed by magma contact metamorphism. It has a hard texture and a Hardgrove grindability index of only 34.5. Its industrial analysis and elemental analysis data are shown in Table 1. The natural coke is crushed to a particle size of <0.074 mm by a jaw crusher and a vibration mill for use in the present invention.

[0037] Table 1 Statistical table of analysis data of natural coke

[0038]

[0039] Note: M ad —Air-dried basis moisture, A d —Dry basis ash, V daf — Volatile matter on dry ash-free basis, C daf —dry ash-free fixed carbon; C d —Carbon content on dry basis, H d —Hydrogen content on dry basis, N d —Nitrogen content on dry basis, S t,d — Total sulfur content on a dry basis, O d — oxygen content on a dry basis; R r —average random reflectivity of the vitrinite group; Q gr,d —Higher calorific value on dry basis; α—CO2 reactivity; ARD—apparent density; HGI—Hardgrove grindability index.

[0040] The purity of magnesium used in the present invention is 98.5wt%, the particle size is <0.074mm, and its X-ray diffraction spectrum is as follows: Figure 1 The instrument used for X-ray diffraction analysis is a SmartLab X-ray diffractometer from Rigaku Corporation of Japan, using copper target Kα rays, with a scanning step size of 0.01° and a scanning speed of 2° / min. Figure 1 It can be seen that magnesium is a relatively pure crystal. According to the 36.5° diffraction peak calculated using the Scherrer formula, the magnesium grain size is >100nm.

[0041] The equipment for ball milling treatment of the present invention is a planetary ball mill. The model of the planetary ball mill is ND8-1L, produced by Nanjing Nanda Tianzun Electronics Co., Ltd. The specific configuration of the planetary ball mill is as follows: 4 ball milling jars are installed, each ball milling jar has a volume of 100 mL, the material of the ball milling jar liner and the grinding balls is sintered zirconium dioxide, the ratio of the number of grinding balls with diameters of 9 mm, 5 mm, and 3 mm is 20:40:40, the ratio of the rotation speed to the revolution speed during operation is 2:1, the rotation direction is the same as the revolution direction, and the revolution is stopped for cooling for 5 minutes after each forward rotation of 5 minutes and reverse rotation of 5 minutes.

[0042] The inert protective gas in the ball mill used in the present invention is preferably argon gas with a purity of 99.999 vol%.

[0043] The ball mill loading and unloading operations of the present invention are carried out in a glove box protected by argon gas. The glove box is a Lab2000 model produced by Etex Inert Gas Systems Co., Ltd. The purity of the argon gas is 99.999 vol%, the oxygen content in the glove box is <0.1 ppm, and the water content is <0.1 ppm.

[0044] The present invention evaluates the hydrogen storage performance of the magnesium-based hydrogen storage material by testing its hydrogen absorption / desorption characteristics. The specific testing method is as follows:

[0045] The hydrogen absorption / desorption characteristics of the material were tested using a high-pressure gas adsorption instrument, which was a PCT-Pro2000 model produced by Setram, France. The material was tested for the 200°C hydrogen absorption kinetic curve, 300°C hydrogen desorption kinetic curve, 300°C cyclic hydrogen absorption / desorption kinetic curve, and 300°C hydrogen absorption / desorption isotherm. During the test, the mass of the solid sample was 300 mg, the hydrogen absorption reference volume was 17.10 mL, the hydrogen desorption reference volume was 176.09 mL, and the free volume of the sample cell was about 11.5 mL at room temperature; during the kinetic test, the initial hydrogen absorption pressure was 2.5 MPa and the initial hydrogen desorption pressure was 0.01 MPa; during the hydrogen absorption isotherm test, the final pressure was 2.0 MPa.

[0046] The present invention is described in detail below by specific examples, which are exemplary and intended to be used to explain the present invention, but cannot be understood as limiting the present invention. In the following examples, the methods are conventional methods unless otherwise specified; the reagents and materials are commercially available unless otherwise specified.

[0047] Example 1

[0048] This embodiment provides a magnesium-based hydrogen storage material, and the preparation method is as follows:

[0049] Step 1: Individual ball milling of natural coke.

[0050] In an argon-filled glove box, 0.122 g of natural coke with analytical data shown in Table 1 was placed in a ball mill, and argon was filled into the ball mill to 3 atm. The ball mill was then milled on a planetary ball mill at a speed of 540 r / min for 1 h to obtain natural coke powder.

[0051] Step 2: ball milling the transition metal pellets and natural coke powder.

[0052] In an argon-filled glove box, 90 nickel metal balls with a diameter of 1.0 mm were added to the ball mill containing the natural coke powder obtained in step 1, and the ball mill was filled with argon to 3 atm, and then ball milled on a planetary ball mill at a speed of 300 r / min for 3 h. In the argon-filled glove box, the nickel metal balls remaining in the ball mill after ball milling were separated by screening to obtain natural coke loaded with transition metals.

[0053] The nickel purity of the nickel metal balls is 99.5wt%; the sieves used for sieving and removing the nickel metal balls remaining after ball milling are sieves with apertures of 1.4mm and 0.5mm. The nickel metal balls between the two aperture sieves are removed by sieving. The mass of the ground nickel is the difference between the masses of the nickel metal balls before and after ball milling. The mass of the ground nickel in this embodiment is 0.031g.

[0054] Step 3: ball milling the magnesium powder and the natural coke loaded with transition metals.

[0055] In an argon-filled glove box, 1.880 g of magnesium powder was added to the ball mill containing the natural coke loaded with transition metals obtained in step 2, and argon was filled into the ball mill to 3 atm. The ball mill was then milled on a planetary ball mill at a speed of 420 r / min for 2 h to obtain a magnesium-based hydrogen storage material.

[0056] The mass proportions of natural coke, nickel and magnesium in the magnesium-based hydrogen storage material prepared in this embodiment are 6.0wt%, 1.5wt% and 92.5wt% respectively.

[0057] The natural coke powder obtained after ball milling in this example and the prepared magnesium-based hydrogen storage material were taken for morphological observation, and the prepared magnesium-based hydrogen storage material was subjected to nickel element distribution analysis, transmission electron microscopy observation, crystal structure analysis, hydrogen absorption / desorption kinetics test, hydrogen absorption / desorption isotherm determination and cyclic hydrogen absorption / desorption stability test.

[0058] The scanning electron microscope photo of the natural coke powder obtained after ball milling in this example is as follows: Figure 2 The instrument used for scanning electron microscope observation is a Hitachi S-570 scanning electron microscope equipped with an energy spectrometer, which can be used for elemental analysis. Figure 2It can be seen that the natural coke powder after ball milling is <1μm, and most of it is <0.1μm.

[0059] The scanning electron microscope photo of the magnesium-based hydrogen storage material of this embodiment is shown in Figure 3 As shown in Figure 1, it can be seen that the particles of magnesium-based hydrogen storage materials are nanometer-sized. The distribution of nickel elements in magnesium-based hydrogen storage materials is shown in Figure 1. Figure 4 As shown, it can be seen that the nickel element is evenly distributed in the material.

[0060] The transmission electron microscope photo of the magnesium-based hydrogen storage material of this embodiment is shown in Figure 5 The instrument used for transmission electron microscopy observation is the H-800 transmission electron microscope produced by Hitachi, Japan. Figure 5 It can be seen that the particles of magnesium-based hydrogen storage materials are nanometer-sized and the particle shapes are mostly hexagonal.

[0061] The X-ray diffraction spectrum of the magnesium-based hydrogen storage material of this embodiment is as follows Figure 6 As shown, the natural coke is amorphous and the magnesium is still crystalline. However, compared with the raw magnesium, the magnesium grains are significantly reduced after ball milling. The grain size calculated by the Scherrer formula based on the 36.5° diffraction peak is 28nm.

[0062] The hydrogen absorption kinetic curve of the magnesium-based hydrogen storage material of this embodiment at 200°C is as follows: Figure 7 As shown in the curve of "Example 1" in the figure, it can be seen that the saturated hydrogen absorption capacity of 6.3wt% can be reached after 2 minutes of hydrogen absorption. The hydrogen release kinetic curve at 300°C is as follows Figure 8 As shown, it can be seen that hydrogen can be completely released in 7 minutes.

[0063] The hydrogen absorption / desorption isotherms of the magnesium-based hydrogen storage material of this embodiment at 300°C are as follows: Fig. 9 As shown, it can be seen that the hydrogen absorption / desorption platform pressure is 0.5 MPa, the pressure difference is 0.15 MPa, and the pressure platform length is 5.5 wt% of hydrogen content.

[0064] The cyclic hydrogen absorption / desorption kinetic curve of the magnesium-based hydrogen storage material of this embodiment at 300°C is as follows: Fig.10 As shown, it can be seen that the amount of hydrogen absorption / desorption of the material does not decay after 45 cycles.

[0065] Example 2

[0066] The difference between this embodiment and embodiment 1 is that the amount of raw material natural coke is reduced to 0.102 g to prepare the magnesium-based hydrogen storage material.

[0067] The contents of natural coke, nickel and magnesium in the magnesium-based hydrogen storage material prepared in this example are 5.1 wt %, 1.3 wt % and 93.6 wt % respectively.

[0068] The hydrogen absorption kinetic curve of the magnesium-based hydrogen storage material prepared in this example at 200°C is as follows: Figure 5 As shown in the curve of "Example 2", it can be seen that the saturated hydrogen absorption amount of 6.3wt% is reached after 12 minutes of hydrogen absorption. Compared with Example 1, the amount of natural coke is reduced and the hydrogen absorption rate is slowed down.

[0069] Example 3

[0070] The difference between this embodiment and embodiment 1 is that the amount of natural coke raw material is reduced to 0.078 g to prepare the magnesium-based hydrogen storage material.

[0071] The contents of natural coke, nickel and magnesium in the magnesium-based hydrogen storage material prepared in this example are 3.9wt%, 1.2wt% and 94.9wt%, respectively.

[0072] The hydrogen absorption kinetic curve of the magnesium-based hydrogen storage material prepared in this example at 200°C is as follows: Figure 5 As shown in the curve of "Example 3", it can be seen that hydrogen absorption has not reached saturation after 12 minutes, and the hydrogen absorption amount is 5.9wt%. The hydrogen absorption rate is significantly slower than that of Example 1, that is, the less the amount of natural coke used, the slower the hydrogen absorption rate of the magnesium-based hydrogen storage material.

[0073] Example 4

[0074] The difference between this embodiment and embodiment 1 is that the amount of natural coke raw material is increased to 0.149 g to prepare the magnesium-based hydrogen storage material.

[0075] The contents of natural coke, nickel and magnesium in the magnesium-based hydrogen storage material prepared in this example are 7.2 wt %, 1.6 wt % and 91.2 wt % respectively.

[0076] The hydrogen absorption kinetics of the magnesium-based hydrogen storage material prepared in this example was measured at 200°C. The saturated hydrogen absorption amount reached 6.2 wt % after absorbing hydrogen for 2 minutes. Compared with Example 1, it can be seen that adding too much natural coke is not beneficial to improving the hydrogen absorption kinetics.

[0077] Example 5

[0078] The difference between this embodiment and embodiment 1 is that the amount of magnesium raw material used is increased to 2.360 g to prepare a magnesium-based hydrogen storage material.

[0079] The contents of natural coke, nickel and magnesium in the magnesium-based hydrogen storage material prepared in this example are 4.9 wt %, 1.2 wt % and 93.9 wt % respectively.

[0080] The magnesium-based hydrogen storage material prepared in this example was used to measure its hydrogen absorption kinetics at 200° C. It was found that the hydrogen absorption had not reached saturation after 12 minutes, and the hydrogen absorption amount was 5.3 wt %.

[0081] Example 6

[0082] The difference between this embodiment and embodiment 1 is that the ball milling speed and the ball milling time are reduced. The ball milling speed of step one is 480 r / min and the ball milling time is 0.5 h, the ball milling speed of step two is 240 r / min and the ball milling time is 2 h, and the ball milling speed of step three is 360 r / min and the ball milling time is 1 h, to prepare a magnesium-based hydrogen storage material.

[0083] The contents of natural coke, nickel and magnesium in the magnesium-based hydrogen storage material prepared in this example are 6.1 wt %, 0.7 wt % and 93.2 wt % respectively.

[0084] The magnesium-based hydrogen storage material prepared in this example was used to measure its hydrogen absorption kinetics at 200° C. It was found that the hydrogen absorption had not reached saturation after 12 minutes, and the hydrogen absorption amount was 3.1 wt %.

[0085] Example 7

[0086] The difference between this embodiment and embodiment 1 is that the ball milling time is reduced, the ball milling time of step one is 0.5 h, the ball milling time of step two is 2 h, and the ball milling time of step three is 1 h, to prepare a magnesium-based hydrogen storage material.

[0087] The contents of natural coke, nickel and magnesium in the magnesium-based hydrogen storage material prepared in this example are 6.0 wt %, 1.3 wt % and 92.7 wt % respectively.

[0088] The magnesium-based hydrogen storage material prepared in this example was used to measure its hydrogen absorption kinetics at 200° C. It was found that the hydrogen absorption had not reached saturation after 12 minutes, and the hydrogen absorption amount was 4.3 wt %.

[0089] Example 8

[0090] The difference between this embodiment and embodiment 1 is that the ball milling time is increased, the ball milling time of step one is 1.5 hours, the ball milling time of step two is 4 hours, and the ball milling time of step three is 3 hours, to prepare a magnesium-based hydrogen storage material.

[0091] The contents of natural coke, nickel and magnesium in the magnesium-based hydrogen storage material prepared in this example are 6.0 wt%, 1.6 wt% and 92.4 wt%, respectively.

[0092] The magnesium-based hydrogen storage material prepared in this example was used to measure its hydrogen absorption kinetics at 200° C. The hydrogen absorption reached saturation after 2 minutes, and the hydrogen absorption amount was 6.2 wt %.

[0093] Example 9

[0094] The difference between this embodiment and embodiment 1 is that the ball milling speed and the ball milling time are increased. The ball milling speed of step one is 600 r / min and the ball milling time is 1.5 h, the ball milling speed of step two is 360 r / min and the ball milling time is 4 h, and the ball milling speed of step three is 480 r / min and the ball milling time is 3 h, to prepare a magnesium-based hydrogen storage material.

[0095] The contents of natural coke, nickel and magnesium in the magnesium-based hydrogen storage material prepared in this example are 6.0 wt %, 1.7 wt % and 92.3 wt % respectively.

[0096] The magnesium-based hydrogen storage material prepared in this example was used to measure its hydrogen absorption kinetics at 200° C. The hydrogen absorption reached saturation after 2 minutes, and the hydrogen absorption amount was 6.1 wt %.

[0097] Example 10

[0098] The difference between this embodiment and embodiment 1 is that the ball milling speed is increased and the ball milling time is reduced. The ball milling speed of step one is 600 r / min and the ball milling time is 0.5 h, the ball milling speed of step two is 360 r / min and the ball milling time is 2 h, and the ball milling speed of step three is 480 r / min and the ball milling time is 1 h, to prepare a magnesium-based hydrogen storage material.

[0099] The contents of natural coke, nickel and magnesium in the magnesium-based hydrogen storage material prepared in this example are 6.0 wt %, 1.5 wt % and 92.5 wt % respectively.

[0100] The magnesium-based hydrogen storage material prepared in this example was used to measure its hydrogen absorption kinetics at 200° C. The hydrogen absorption reached saturation after 2 minutes, and the hydrogen absorption amount was 6.2 wt %.

[0101] Embodiment 11

[0102] The difference between this embodiment and embodiment 1 is that the ball milling speed is reduced and the ball milling time is increased. The ball milling speed of step one is 480 r / min and the ball milling time is 1.5 h, the ball milling speed of step two is 240 r / min and the ball milling time is 4 h, and the ball milling speed of step three is 360 r / min and the ball milling time is 3 h, to prepare a magnesium-based hydrogen storage material.

[0103] The contents of natural coke, nickel and magnesium in the magnesium-based hydrogen storage material prepared in this example are 6.0 wt %, 1.4 wt % and 92.6 wt % respectively.

[0104] The magnesium-based hydrogen storage material prepared in this example was used to measure its hydrogen absorption kinetics at 200° C. The hydrogen absorption reached saturation after 2 minutes, and the hydrogen absorption amount was 6.1 wt %.

[0105] Example 12

[0106] The difference between this embodiment and embodiment 1 is that the transition metal used as a catalyst is iron, that is, iron metal balls are used instead of nickel metal balls to prepare magnesium-based hydrogen storage materials.

[0107] The contents of natural coke, iron and magnesium in the magnesium-based hydrogen storage material prepared in this example are 6.0 wt%, 1.7 wt% and 92.3 wt%, respectively.

[0108] The magnesium-based hydrogen storage material prepared in this example was used to measure its hydrogen absorption kinetics at 200° C. The hydrogen absorption reached saturation after 12 minutes, and the hydrogen absorption amount was 5.7 wt %.

[0109] Embodiment 13

[0110] The difference between this embodiment and embodiment 1 is that the transition metal used as a catalyst is cobalt, that is, cobalt metal pellets are used instead of nickel metal pellets to prepare the magnesium-based hydrogen storage material.

[0111] The contents of natural coke, cobalt and magnesium in the magnesium-based hydrogen storage material prepared in this example are 6.0 wt %, 1.2 wt % and 92.8 wt % respectively.

[0112] The magnesium-based hydrogen storage material prepared in this example was used to measure its hydrogen absorption kinetics at 200° C. The hydrogen absorption reached saturation after 2 minutes, and the hydrogen absorption amount was 5.9 wt %.

[0113] Embodiment 14

[0114] The difference between this embodiment and embodiment 1 is that the transition metal used as a catalyst is a mixture of iron, cobalt and nickel in an equiatomic ratio, that is, 30 iron metal balls and 30 cobalt metal balls are used to replace 60 nickel balls, and 30 nickel metal balls are retained to prepare a magnesium-based hydrogen storage material.

[0115] The contents of natural coke, iron-cobalt-nickel and magnesium in the magnesium-based hydrogen storage material prepared in this example are 6.0 wt %, 1.6 wt % and 92.4 wt % respectively.

[0116] The magnesium-based hydrogen storage material prepared in this example was used to measure its hydrogen absorption kinetics at 200° C. The hydrogen absorption reached saturation after 2 minutes, and the hydrogen absorption amount was 6.1 wt %.

[0117] Comparative Example 1

[0118] The difference between this comparative example and Example 1 is that only magnesium powder is used as the raw material, and natural coke and transition metal are not used. The specific steps are as follows:

[0119] In a glove box protected by argon, 1.880 g of magnesium powder was added to a ball mill, and argon was filled into the ball mill to 3 atm. The ball mill was milled at a speed of 420 r / min for 2 h in a planetary ball mill to obtain a magnesium-based hydrogen storage material.

[0120] The hydrogen absorption kinetics of the magnesium-based hydrogen storage material prepared in this comparative example at 200°C and the hydrogen release kinetics at 300°C were measured. The hydrogen absorption amount at 200°C for 12 minutes was only 0.2wt%, and the hydrogen release amount at 300°C for 12 minutes was only 0.1wt%. It was also observed that magnesium powder without natural coke and transition metal addition would "cold weld" to the grinding balls and the inner surface of the ball mill during ball milling.

[0121] The statistical results of the composition of the magnesium-based hydrogen storage materials obtained in Examples 1 to 14 and Comparative Example 1 are shown in Table 2.

[0122] Table 2 Statistical results of the composition of magnesium-based hydrogen storage materials

[0123]

[0124]

[0125] The statistical results of the hydrogen absorption performance of the magnesium-based hydrogen storage materials in Examples 1 to 14 and Comparative Example 1 at 200°C are shown in Table 3.

[0126] Table 3 Statistical results of hydrogen absorption performance of magnesium-based hydrogen storage materials at 200°C

[0127]

[0128] It can be seen from the above experimental results that, compared with Comparative Example 1, the hydrogen storage performance of the magnesium-based hydrogen storage materials in Examples 1 to 14 is significantly improved, among which the hydrogen storage performance of the magnesium-based hydrogen storage material in Example 1 is better.

[0129] Combination Figures 2 to 8 , indicating that by using transition metal pellets as the precursor of transition metal catalysts and natural coke as the carrier of transition metal catalysts, and grinding the transition metal off the surface of the pellets by ball milling, a highly dispersed transition metal catalyst can be obtained; using natural coke as a grinding aid for ball milling of magnesium powder, its good dispersing effect and grinding medium effect can prevent "cold welding" between magnesium particles, making it easy to grind magnesium powder to nanometer level, and effectively improving the hydrogen absorption / desorption kinetics of magnesium. That is, the preparation method of magnesium-based hydrogen storage material provided by the present invention can solve the technical problem of difficulty in achieving high dispersion of transition metal catalysts and nanometerization of magnesium powder, and effectively improve the hydrogen storage performance of magnesium-based hydrogen storage materials.

[0130] Therefore, the preferred process conditions for preparing magnesium-based hydrogen storage materials with fast hydrogen absorption and desorption rates and large hydrogen absorption capacity are: transition metal nickel is used as the catalyst, the ball milling speed of natural coke alone is 540r / min and the ball milling time is 1h, the ball milling speed of transition metal balls added to natural coke powder for mixed ball milling is 300r / min and the ball milling time is 3h, the ball milling speed of magnesium powder added to natural coke loaded with transition metal for mixed ball milling is 420r / min and the ball milling time is 2h, and the optimal composition of magnesium-based hydrogen storage materials is natural coke, nickel and magnesium accounting for 6.0wt%, 1.5wt% and 92.5wt% respectively.

[0131] The above description is only a preferred embodiment of the present invention, and the above specific embodiment is not intended to limit the present invention. Various deformations and modifications may occur within the scope of the technical concept of the present invention, and any modification, modification or equivalent replacement made by a person of ordinary skill in the art based on the above description shall fall within the scope of protection of the present invention.

Claims

1. A method for preparing a magnesium-based hydrogen storage material by adding natural coke and transition metals, characterized in that: The steps include: Under a protective atmosphere, natural coke is ball-milled to obtain natural coke powder; Under a protective atmosphere, adding transition metal pellets to the natural coke powder obtained by ball milling, mixing and ball milling, and then separating the remaining transition metal pellets after ball milling to obtain natural coke loaded with transition metals; Under a protective atmosphere, adding magnesium powder to the natural coke loaded with transition metals obtained by ball milling, and mixing and ball milling, to obtain a magnesium-based hydrogen storage material with added natural coke and transition metals; The mass proportions of the components in the magnesium-based hydrogen storage material are as follows: 3.9wt% to 7.2wt% of natural coke, 0.7wt% to 1.7wt% of transition metals, and 91.2wt% to 94.9wt% of magnesium, wherein the transition metal is at least one of iron, cobalt and nickel.

2. The method for preparing a magnesium-based hydrogen storage material according to claim 1, characterized in that: The ball milling speed of the natural coke single ball milling is 480r / min-600r / min, and the ball milling time is 0.5h-1.5h.

3. The method for preparing a magnesium-based hydrogen storage material according to claim 1, characterized in that: The transition metal balls and natural coke powder are mixed and ball-milled at a ball-milling speed of 240 r / min to 360 r / min, and the ball-milling time is 2 h to 4 h.

4. The method for preparing a magnesium-based hydrogen storage material according to claim 1, characterized in that: The ball milling speed of the mixed ball milling of the magnesium powder and the natural coke loaded with transition metals is 360 r / min to 480 r / min, and the ball milling time is 1 h to 3 h.

5. The method for preparing a magnesium-based hydrogen storage material according to claim 1, characterized in that: The mass ratio of the transition metal pellets to the natural coke powder is 2 to 5:

1.

6. A magnesium-based hydrogen storage material, characterized in that: The magnesium-based hydrogen storage material is prepared by the preparation method of any one of claims 1 to 5.

Citation Information

Patent Citations

  • Method for enhancing dehydrogenating property of magnesium-based hydride

    CN105460892A

  • Nanometer magnesium base reversible hydrogen storage composite material and preparation method thereof

    CN105734323A

  • Preparation method of heteroatom-like catalyst

    CN110586102A

  • Preparation method and application of carbon-based transition metal monatomic material

    CN113413903A

  • Magnesium-base hydrogen storage material having added transition metal oxide

    CN1429923A

Cited By

  • MOF-coated MWCNTs composite catalyst modified magnesium-based hydrogen storage composite material and preparation method thereof

    CN122355231A